Australian Paediatric Hyperbaric Oxygen Therapy 1998–2011. Issue 1 (January 2013) - Frawley, G.; Bennett, M.; Thistlethwaite, K.; Banham, N.
For a large number of ischaemic, infective, inflammatory or traumatic conditions, hyperbaric oxygen therapy is either the only treatment or an adjunct that significantly reduces morbidity and mortality. The primary aim of this review is to identify clinical conditions treated in a paediatric population referred to Australian hyperbaric units. Secondary aims are to describe outcomes of treatment and detail any complications occurring during treatment or during transfer between units. This was a retrospective cohort study (January 1998–December 2011) of children treated at four Australian hyperbaric medical units. A total of 112 children underwent 1099 hyperbaric treatments for 14 indications. Ages were not normally distributed with a median age of 14 years (interquartile range 11–16; range 0.25–16 years). Treatments were completed as planned in 81.5% of cases with 25 patients' treatment terminated at the request of physicians, parents or patients. Complications relating to hyperbaric oxygen therapy occurred in 58 treatments (5.3%). Central nervous system oxygen toxicity occurred in 1:366 treatments. Our findings indicate that provision of hyperbaric oxygen therapy to children is feasible in major regional hyperbaric units and is associated with low complication rates. Management of children in an adult hyperbaric facility, however, requires significant cooperation between paediatric, intensive care and hyperbaric consultants, as the need for transfer to another hospital and prolonged transports often impacts on optimal ongoing surgical and intensive care management.